Control of Electric Drives in the Best Efficiency Region of Pumping System - Bakman, Ilja (Electrical, Control and Communication Engineering, 2014)
The paper concentrates on improving the efficiency of the pumping system in which pumps are run by variable speed drives. The method is applicable to system consisting of several centrifugal pumps. Problems arising from running the pumps outside the optimal efficiency region are discussed. Common principles of operation and control of typical boosting pumping station are represented. Methods of regulation of productivity of the system are described. The proposed method is based on prediction of future efficiency of pumps before making adjustments of pumping system productivity. The proposed method is basing on tracking the working point of pump on efficiency graph. Monitoring the location of working point vs. efficiency graph enables to evaluate its current and future distances from the best efficiency point of the pump. Knowing the current number of running pumps it is possible to predict the location of working point after adjustment of productivity of the system. Ability to predict the increase or decrease of efficiency enables to enhance the adjustment of productivity of the system. Methods of graphical analysis of working state of the pumping system are representing topic for future research.